KEBUTUHAN MENINGKATKAN MUTU GURU DALAM PROSES PEMBELAJARAN MELALUI AKREDITASI DI SEKOLAH DASAR - Wahira Wahira; Abdul Hamid (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2024)
School accreditation has a very important role in improving the quality of teachers. because school accreditation helps set educational quality standards that must be met by educational institutions. The objectives of this study are: (1) to get an overview of the importance of elementary school accreditation; (2) to get an overview of the importance of improving the quality of teachers in elementary schools. R & D research methods with qualitative descriptive research type. The respondents were 30 elementary school teachers in Jeneponto Regency, South Sulawesi. The results of his research illustrate that school accreditation needs to be carried out in very necessary categories, And the quality of teachers needs to be improved by the category of need. Because accreditation provides a legal framework for educational institutions. The existence of an accreditation body can help ensure that the institution operates by applicable norms and regulations in improving the quality of teachers.